Sexual Disorders in the DSM-5: Implications for Counselors. Issue 1 (1st January 2016) - Zeglin, Robert J.
Abstract : Th e Diagnostic and Statistical Manual of Mental Disorders (DSM) is one of the most important mediums through which counselors receive information on the evolving nature of the profession. Such evolution is exemplified by the DSM- 5 and its updated conceptualization of sexual disorders. The present article seeks to: a) Outline the key changes in sexual disorders in the DSM-5, b) Offer practical literature-based suggestions for best practice related to said changes, and c) Offer implications for counselor education.